Evaluation Of The Implementation Of Character Education Policy In Madrasah Miftahul Huda, Sungai Malaya Village, Kubu Raya Regency - Saiful Umam (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2019)
This study aims to evaluate the application of character education policies at MI Miftahul Huda Sungai Ambawang District, Kubu Raya Regency. The evaluation process is carried out at the implementation stage of the policy, including understanding implementation, implementation constraints, and evaluating the strategies used in overcoming obstacles to the implementation of character education policies. This type of research is qualitative descriptive. The process of collecting data is done through observation, in-depth interviews, and analysis of related documents. The stages in data analysis are done by presenting data, reducing data, and then making conclusions. The results showed that the implementation of character education policies at MI Miftahul Huda in Kubu Raya District did not work well, the obstacles that occurred during the implementation were related to poor example given by teachers and parents, lack of professionalism of teachers and lack of involvement of parents and the community. Therefore, efforts need to be made to change the mindset of parents and society that character education is better starting from the family and the environment, and there must be an effort to improve teacher professionalism, accompanied by the active role of the relevant Education Agency, which can be material or moral assistance.